Retoryka i socjo-retoryka w lekturze tekstów Nowego Testamentu Cz. 2: Socjo-retoryka – projekt holistycznej lektury tekstu - Kowalski, Marcin (The Biblical Annals, 2017)
In the second part of the article on the rhetorical and socio-rhetorical reading of New Testament texts, the author focuses on the socio-rhetorical approach. It is presented as a remedy to the fragmentary character of the sociological and anthropological studies on the Bible. The stress on the close reading of the text inherent in the socio-rhetoric gives both sociology and anthropology the anchorage they need not to stray from the main object of their inquiry. The author with broad strokes depicts the development and main concepts of the socio-rhetorical methodology. Then, he explains the six stages postulated by the method: the analysis of inner texture, intertexture, social and cultural texture, ideological texture, sacred texture, and the so called rhetorolects. The article finishes with concise conclusions on the advantages of using the socio-rhetoric in comparison to the deficient historical-critical methodology